South Korea's development renaissance and its impact on its international standing (Tikrit Journal For Political Science, 2024)
South Korea's development experience has provided the world with lessons for a successful and unique experience. Among the geopolitical determinants of the country's small area, harsh terrain, scarcity of energy and natural resources, as well as its geopolitical location, which placed it in a hot and difficult regional environment. Despite all these determinants and constraints, South Korea has provided A renaissance and a successful experience that dazzled the world, transforming South Korea from a country that lived on foreign aid to an advanced civilized country at all levels, This renaissance was reflected in the country's standing, and it recorded its name in gold among the list of big  on the global level.